ANALISIS KAJIAN STRUKTUR DESAIN TERHADAP MUTU EXISTING PADA PENAMPANG NON PRISMATIC GABLE FRAME PT UNIMOTOR TECHNOLOGY INDONESIA - Teguh Mulyo Wicaksono; Moh. Abduh; Dwi Respono Adhi; Ridho Wicaksono; Puspa Anandhita Fristio; Vera Mahardika; Rajna Maulia Dwi Rahma (Politeknik Negeri Semarang, 2026)
The use of non-prismatic gable frame steel structures is common in industrial buildings due to their structural efficiency. However, their performance depends significantly on the quality of the steel material. This study evaluates the mechanical properties of Chinese structural steel grade Q355B (GB/T 1591-2018) and assesses its structural performance in a non-prismatic gable frame system at PT Unimotor Technology Indonesia. A quantitative approach was employed through laboratory testing using the Brinell and Rebound methods to determine steel hardness and ultimate tensile strength (Fu). The test results showed a minimum Fu value of 495 MPa. Nevertheless, conservative design properties specified for Q355B steel (Fy = 355 MPa and Fu = 470 MPa) were adopted in the structural analysis. A three-dimensional model was developed using CSI ETABS V.21.0 to represent the non-prismatic gable frame geometry. Structural analysis was conducted in accordance with SNI 1727:2020, SNI 1726:2019, and LRFD load combinations, considering dead, live, wind, and seismic loads. The results indicate that all structural members satisfy the required strength criteria. The maximum flexural–shear interaction ratio was 0.601, while the flexural–compression interaction ratio was 0.57, both below the allowable limit of 1.0. The structure also met the requirements for lateral-torsional buckling resistance. Based on the analysis, the non-prismatic gable frame system using Q355B steel is structurally safe and complies with the requirements of SNI 1729:2020.